2022
DOI: 10.1186/s12903-022-02402-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the absence of Brazilians in specialized dental centers

Abstract: Aim To identify the individual and contextual factors associated with the absence of Brazilians at a scheduled appointment in Dental Specialties Centers (DSC). Methods This cross-sectional design uses the National Program for Improving Access and Quality of Dental Specialties Centers database, 2018. The outcome was the users' lack of at least one of the scheduled appointments. Contextual and individual independent variables were used, considering A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
5
0
4
Order By: Relevance
“…It is of fundamental importance to identify adolescents with untreated dental caries to schedule an appointment in primary health care [ 24 ], especially for the most vulnerable adolescents [ 24 ]. This can help with the principle of equity in universal health coverage, giving more attention to those who need it most.…”
Section: Discussionmentioning
confidence: 99%
“…It is of fundamental importance to identify adolescents with untreated dental caries to schedule an appointment in primary health care [ 24 ], especially for the most vulnerable adolescents [ 24 ]. This can help with the principle of equity in universal health coverage, giving more attention to those who need it most.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with previous studies such as that by Cunha et al, which demonstrated that patients younger than 42 years old have higher missed appointments, as well as other studies that explained that young adults are potentially less likely to miss work or school days to attend a dental or medical appointment. 35 Similarly, Nelson et al demonstrated that young caregivers (younger than 31 years of age) were more likely to miss a child's pediatric dental appointment compared to older caregivers, even with the use of SMS text message reminders. 36 Hence, a solution that could help prevent this is to offer appointments during alternative off-work schedules such as lunch breaks and weekend.…”
Section: Discussionmentioning
confidence: 99%
“…36 Hence, a solution that could help prevent this is to offer appointments during alternative off-work schedules such as lunch breaks and weekend. 35,37 Noteworthy, because many studies report age groups with different ranges, comparing results based on patient's age is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De forma semelhante, esses programas poderiam influenciar o uso do serviço odontológico, mesmo que tal atendimento não faça parte das condicionalidades exigidas por alguns programas, como no caso do Bolsa Família. Evidência recente sobre o efeito de programas de transferência de renda é inconclusiva, no entanto, indica que o uso de serviços odontológico parece não aumentar 11 , 12 , 13 , 14 , 15 .…”
Section: Introductionunclassified